12x+3=18x-3

Simple and best practice solution for 12x+3=18x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x+3=18x-3 equation:


Simplifying
12x + 3 = 18x + -3

Reorder the terms:
3 + 12x = 18x + -3

Reorder the terms:
3 + 12x = -3 + 18x

Solving
3 + 12x = -3 + 18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18x' to each side of the equation.
3 + 12x + -18x = -3 + 18x + -18x

Combine like terms: 12x + -18x = -6x
3 + -6x = -3 + 18x + -18x

Combine like terms: 18x + -18x = 0
3 + -6x = -3 + 0
3 + -6x = -3

Add '-3' to each side of the equation.
3 + -3 + -6x = -3 + -3

Combine like terms: 3 + -3 = 0
0 + -6x = -3 + -3
-6x = -3 + -3

Combine like terms: -3 + -3 = -6
-6x = -6

Divide each side by '-6'.
x = 1

Simplifying
x = 1

See similar equations:

| 27w/-12w | | 4(m+4)+8(-12m+11)=m-8+8m+11 | | 8(w-84)=88 | | 81=-9(j+87) | | 5(p-65)=85 | | -7(t-9)+2t=-8+t | | 27-m=8 | | 2x/4-1/4=x/3-7/3 | | 4a-11=9+3a | | 5(-6+1)-4n=-5+2n | | 24=-3(t+-24) | | 2(n-52)-22=2 | | 2(t-64)=56 | | 67-z=40 | | 2(s+1)=10 | | 4(s-90)=-50 | | (5x-6)(x^2-4x-1)= | | (4x^2)-47+70=0 | | M-52=27 | | 3(v+2)=12 | | 3(b+1)+1=10 | | 3(z+-15)=-60 | | 25-w=46 | | 16=-2(n+-17) | | m^2-n^2-am-an=0 | | 6-2x=-20 | | 15p+19.96=-14.08+11.3p | | 2(3r-7)-(2+r)= | | -11.4u-3.54+19.2u=8.34+8.9u | | -5.6k-16.61=-4.5k | | -13.03+5.1m=12.3m+10.01 | | -12.2w+16.74=-13.6w-7.2 |

Equations solver categories